Altruism among University Students: A Study of Transactional Analysis Ego States and Life Satisfaction - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2015)
The aim of this study is to determine whether or not university students' Transactional Analysis (TA) Ego States and life satisfaction predict their altruistic behaviors. Accordingly, Altruistic Behavior Scale, TA Ego States Scale and The Satisfaction with Life Scale were used in data collection. The sample of the study consisted of 299 female and 237 male students studying at the different faculties of Marmara University. Results indicated that only the Nurturing Parent Ego States, one of the TA Ego States, significantly predicted the altruistic behavior of students, whereas the other ego states had no effect on prediction. Also, life satisfaction of students predicted their altruistic behaviors. When Nurturing Parent Ego States and life satisfaction came together, they strongly predicted altruistic behavior. Finally, this study discusses the collected data within the related literature, and some suggestions are put forth.
Keywords: Altruism; Pro-social Behavior; Personality; Positive Psychology; Values; BEHAVIOR